From softening polymers to multimaterial based bioelectronic devices. Issue 1 (11th December 2018) - Ecker, Melanie; Joshi-Imre, Alexandra; Modi, Romil; Frewin, Christopher L.; Garcia-Sandoval, Aldo; Maeng, Jimin; Gutierrez-Heredia, Gerardo; Pancrazio, Joseph J; Voit, Walter E.
Abstract: A recent development in bioelectronic devices involves the utilization of multifunctional polymers as substrate material. Dynamically softening, thin-film polymers reduce the mechanical mismatch between device and tissue after implantation and therefore improves the device–tissue interaction. However, when implementing a new material into the fabrication of fully functional and chronically viable devices, there are specific challenges that need to be addressed. The key for all multimaterial devices is to ensure a good adhesion and connectivity between the different layers. That is especially true if one of the materials is sensitive to stimuli such as temperature and moisture. This review will give an overview on the development of a variety of neural interfaces for recording and stimulation with softening shape memory polymers (SMPs) as substrate material. This review discusses specific requirements for device fabrication, testing, and durability.